2020
DOI: 10.3390/ma13061401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetic Head Shape on Processing of Titanium Alloy Wire by Magnetic Abrasive Finishing

Abstract: Titanium alloy wire is characterized by high specific strength, good corrosion resistance, high-temperature resistance and other excellent comprehensive performance. It has been widely used not only in aerospace, shipbuilding and other high-tech fields, but also increasingly in medical equipment, food safety and other fields. Because titanium alloy wire is relatively difficult to process, it has a large deformation resistance, good elasticity, high flexion ratio and more serious rebound. During the processing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The optimum parameters that was used to achieve this improvement were feed rate of 15000 mm/min, spindle rotational feed of 900 rpm, 15% shear thickening fluid and 0.8 mm working gap. Li et al [159] showed that the shape of the magnetic head had significant influence on the performance of MAF when used for surface polishing of 1 mm Ti-6Al-4V wire. They investigated different taper angles (0, 25, 35°) and found that at taper angle of 37°, tool speed of 800 rpm, processing time of 300s and abrasive particle size of 178 mm, the surface roughness of 1 mm Ti-6Al-4V wire was reduced to 0.28 mm from 0.9 mm.…”
Section: Magnetic Abrasive Finishingmentioning
confidence: 99%
“…The optimum parameters that was used to achieve this improvement were feed rate of 15000 mm/min, spindle rotational feed of 900 rpm, 15% shear thickening fluid and 0.8 mm working gap. Li et al [159] showed that the shape of the magnetic head had significant influence on the performance of MAF when used for surface polishing of 1 mm Ti-6Al-4V wire. They investigated different taper angles (0, 25, 35°) and found that at taper angle of 37°, tool speed of 800 rpm, processing time of 300s and abrasive particle size of 178 mm, the surface roughness of 1 mm Ti-6Al-4V wire was reduced to 0.28 mm from 0.9 mm.…”
Section: Magnetic Abrasive Finishingmentioning
confidence: 99%
“…They described that the most significant parameters were working gap and speed. Li et al [20] processed titanium alloy wire by MAM. They reported that under the same processing time the surface finish was improved to 0.28 µm by MAM.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic abrasive finishing is used in different kinematic variations for machining flat surfaces [1][2][3][4][5][6][7][8][9][10][11], shafts [12][13][14], thin-walled tubes [15][16][17][18][19], wires [20,21], cutting tools [22][23][24] and freeform surfaces [25][26][27]. However, this usually requires separate equipment, which increases the time and costs involved.…”
Section: Introductionmentioning
confidence: 99%